Receptivity to Assessment-based Feedback for Management Development - Brutus, Stephane (Institutional Knowledge at Singapore Management University, 1998)
Research on feedback acceptance typically has not focused on feedback given in developmental contexts nor has this research used sources other than self-reports to measure feedback acceptance. This study examined recipient characteristics as influences on receptivity to management development feedback. Racial similarity of the feedback recipient and giver was the most consistent predictor of receptivity. Self-report, feedback giver, and outsider ratings of receptivity evidenced little congruence. Implications for understanding receptivity in developmental contexts are discussed.